Analisis Pengaruh Persepsi Kemudahan, Manfaat, Kenyamanan Terhadap Keputusan Pembelian Online Studi Kasus Layanan Gopay - Putri, Nurul Ihsani (Journal of Entrepreneurship, Management and Industry (JEMI), 2021)
Internet and digital communication are substantial elements that drive the development of today’s marketing science and practice. These elements contribute largely toward the shifts in online products and services’ marketing strategies at the international level. The author assumes that the perceptions of ease, benefit and comfort are important elements for the post-graduate (here masters) student in Universitas Bakrie Jakarta to use Go-Pay, a digital wallet software embedded in Gojek application to complete online purchases. This research analys the impact of perceptions of ease, benefits, and confort on the purchase of of Go-Pay. Respondents were Masters students of Bakrie University who use go-Pay. The results showed that ease, benefit, and comfort, had positive and significant impacts on the purchase of Go-Pay. It is recommended that Gojek management, as the service provider, carry out constant evaluations and continuous developments on the basis of user’s complaints so that they become loyal customers